Depth of relationship counseling review counselor version - Sisca Folastri; M. Ramli (Universitas Negeri Padang, 2022)
The depth of the relationship in counseling is key in determining the success of counseling. The method used in this study is the survey method. The sample in the study involved as many as 36 counselors. The instrument used is the Rational Depth Frequency Scale (RDFS). The data analysis technique uses Rasch modeling with the winstep program version 4.45. Researchhas revealed that in general counselors have a depth of relationship in the counseling process. Where the counselor in the moment of depth of the relationship feels intense security, genuineness, empathy, and positive acceptance in the counseling process. The counselor feels what the counselor is going through, the counselor openly conveys his problems because of the counselor's warm and pleasant acceptance attitude. The depth of the counselor relationship in the counseling process as one of the factors of success and effectiveness of counseling. The results of this study can be used as preliminary data to examine more deeply the depth of the relationship in the counseling process in terms of counseling